An iron germylene complex having Fe–H and Ge–H bonds: synthesis, structure and reactivity. Issue 25 (13th June 2017) - Dhungana, Tara Prasad; Hashimoto, Hisako; Tobita, Hiromi
Abstract : An iron germylene complex having Fe–H and Ge–H bonds was synthesized and its reactivity toward various organic substrates was investigated. Abstract : A base-free iron germylene complex Cp*(CO)(H)Fe{GeHC(SiMe3 )3 (1 ) was synthesised by abstraction of pyridine from a germyl complex Cp*(CO)(py)FeGeH2 C(SiMe3 )3 (2 ), which was prepared by treatment of Cp*Fe(CO)(py)(Me) with H3 GeC(SiMe3 )3 . X-ray crystallographic analysis revealed that1 has an Fe–Ge bond that is the shortest among those ever reported. Reactivity of1 toward several polar unsaturated organic compounds was investigated. Complex1 underwent stoichiometric hydrogermylation of carbonyl compounds such as ketones, aldehydes and isocyanates (RNCO) at room temperature. In contrast, the reactions of1 with isothiocyanates (RNCS) resulted in clean cleavage of the C{S double bonds.